Unravelling Third Space as Urban Design Quality through Behavior Mapping in Kayutangan Street, Malang, Indonesia - Esperanza, Dhiba; Ernawati, Jenny; Kusdiwanggo, Susilo (RUAS, 2025)
The third space is an interaction space that connects spatiality, history, and social aspects. As a space that surpasses other spaces, the third room should also show good urban design quality. This study seeks to reveal the characteristics of the Third Space in the historical street of Kayutangan and its relationship with the Quality of Urban Design through behavior mapping techniques based on Naturalistic Observation. The research uses a qualitative approach with observation units of activity type, frequency, direction of face, spatial distance, duration of activity, gender, age, and environmental stimulus in observing the character of the Third Space. This unit was analyzed using the dimensions of imageability: sense of place, place identity, and attractiveness. It was found that there are 13 symptoms of the Third Space in the area and their relationship with the quality of urban design. These aspects are the heterogeneity of activities, the participation of informal actors, the existence of street vendors, cultural heritage, permeability, sense of healing, sense of navigation, sense of reflection, architectural didacticism, the completeness of street furniture, social interaction, interaction between street furniture and informal actors, and the existence of iconic buildings.